Hermeneutic Study in The Novel “Tuyet” Bur Rasuanto's Works - Tuti Herawati (Journal of Scientific Research, Education, and Technology (JSRET), 2023)
The purpose of this research is to describe hermeneutics in the novel Tuyet by Bur Rasuanto. This research is a type of library research. Source of data in this research is primary and secondary data. Primary data is the main data taken from the novel Tuyet by Bur Rasuanto and secondary data is taken from several literatures that support primary data. The method used to obtain data in this study is a qualitative descriptive analysis method, namely reading repeatedly and then analyzing and recording words, sentences, expressions that contain hermeneutics. After the data is collected, the data is analyzed by identifying the data based on the problem items and research objectives. From the results of the analysis above, it can be concluded that the novel Tuyet by Bur Rasuanto is full of meaning. The novel teaches us that the amount of love for parents can cripple the human mind. In addition, living with idealism will lead humans to exile to the ruling regime. The more dangerous is that power that is too prominent also increasingly acts arbitrarily against its own people which is also capable of diminishing the spirit of human life.